Validação para a população brasileira da escala de dominância télica (TDS) no contexto esportivo - Balbim, Guilherme Moraes (2013)
The purpose of this study was to validate to portuguese language and brazilian population the Telic Dominance Scale (TDS). Participated four translators and three Phd in sports psychology who were involved in the processes of translation, adaptation and content validation to portuguese language of TDS. The sample was composed of 293 athletes of 15 cities of Paraná state participants of 2012 Parana' Open Games final phase and 98 athletes of Jundiaí-SP participants of 2012 Interior Open Games, with total sample of 391 athletes, 204 male and 187 female, of 13 team and individuals modalities: basketball (90), handball (87), athletics (36), volleyball (31), indoor football (29), swimming (26), taekwondo (21), football (19), cycling (17), tennis (13), rhythmic gymnastics (09), rugby (08) and beach volleyball (05). The validation instrument was the Telic Dominance Scale (TDS), composed of 42 items with three options for certain situations. It was used the back translation method, analysis of content validity, descriptive analysis of data by mean values (X), standard deviation (SD), minimum and maximum. Was verified TDS internal consistency for Portuguese language through Cronbach's alpha, temporal stability (test-retest reliability) by intraclass correlation coefficient and construct validity by the confirmatory factorial analysis. Results demonstrated that 12 items were excluded from the TDS portuguese version due insufficient values in validation content coefficient; the internal consistency of two dimensions of the instrument were satisfactory (α =0,75 and α =0,74), but one dimension was below the recommended (α =0,44); showed good temporal stability by intraclass correlation coefficient ranging between r=0,90 and r=0,98; regarding construct validity, 13 items were excluded from TDS portuguese version because they did not present individual reliability; generally, the values of absolute, incremental and parsimonious model fit indicators of TDS with 17 items (X2 = 216.26, GL = 117, P = 0.001, X2 / df = 1.84, GFI = 0.94, RMR = 0.09, RMSEA = 0.04, TLI = 0.82, NFI = 0.81, AGFI = 0.92, CFI = 0.90, ECVI = 0.72) expressed acceptable construct validity of the portuguese version. The "Escala de Dominância Télica" (TDS), portuguese language version of Telic Dominance Scale (TDS) is valid and reliable for use in the brazilian context.